Gestão dos stakeholders em projetos BIM (building information modeling) na indústria da construção: proposta de framework de identificação e classificação de stakeholders - Cardoso, Aline Michelle (2022)
For the implementation of BIM (Building Information Modeling) the participation and commitment of stakeholders and collaborative approaches are important, but the literature and empirical data have shown that these stakeholders are neglected with regard to identification, whether during BIM project management or management of stakeholders in BIM projects, both within the context of the construction industry. The general objective of this research is to develop a proposal for a framework for identifying and classifying stakeholders in BIM projects in the construction industry. This thesis is composed of 3 studies. Study 1 mapped the themes of BIM project management in the construction industry, through a systematic literature review that analyzed bibliographic variables, keywords and in-depth analysis, with a sample of 20 studies that met the research scope. In study 1, (12) themes and (6) thematic groupings of BIM project management in the construction industry were identified, in addition to the argument about the negligence made to stakeholders. Study 2 analyzed the determining factors for stakeholder management in BIM projects in the construction industry, and bibliometrics was performed with subsequent content analysis, with a sample of 124 documents published from 2013 to 2021 in 56 different sources. In study 2, (7) determining factors were found for the management of stakeholders in BIM projects in the construction industry, which are subdivided into (32) items, and presented (26) types of neglected stakeholders and their respective actions of power, legitimacy and urgency (Mitchell et al., 1997). And study 3 developed a proposal for a framework for identifying and classifying stakeholders for the identification phase of stakeholder management in BIM projects in the construction industry. Study 3 was based on the Design Science Research method and interviews were conducted with key stakeholders in the management of stakeholders in BIM projects (construction companies, management and project companies, government project management companies, and material / equipment manufacturers), this study brought a technological product. The contribution of this thesis is a proposed framework aimed at identifying and classifying stakeholders in BIM projects in the construction industry. The framework refers to phase 1 of a generic stakeholder management model, which is composed of 4 phases, identification, planning, engagement and control. As future studies, the other phases of the generic model, or the conceptual model of the stakeholder relationship, or the stakeholder identification model with interference from the attributes of power and legitimacy can be explored.